Analisis Yuridis Terhadap Pelanggaran Hak Asasi Manusia yang Dilakukan Oleh Civilian Combatants dalam Konflik Bersenjata Internasional - Jessica Carina Baptista Ferreira; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This article examines the legal ambiguities surrounding the status of civilians actively engaged in hostilities (civilian combatants) within the framework of International Humanitarian Law (IHL) and International Human Rights Law (IHRL). While the 1949 Geneva Conventions and the 1998 Rome Statute establish a clear demarcation through the distinction principle, the phenomenon of direct participation in hostilities (DPH) poses a significant legal challenge, as civilians forfeit their protected status upon taking part in combat. Using a normative-legal approach, this study analyzes how acts of violence committed by armed civilians can be categorized as war crimes, crimes against humanity, or gross human rights violations. The findings demonstrate that civilian status does not grant impunity for individuals who commit atrocities. Under the principle of individual criminal responsibility, the International Criminal Court (ICC) and national tribunals possess the jurisdiction to prosecute offenders, regardless of their formal military standing. Such legal enforcement is paramount to upholding the integrity of humanitarian principles and ensuring justice for victims within the landscape of modern armed conflict.